The critical role of class tutor in family-school partnership - Zenhas, Armanda (International Journal about Parents in Education, 2023)
In the Portuguese school system the class tutor is a teacher who plays a pivotal role in bridging schools and families. The purpose of this study is to describe the innovative project of school-family partnership at class level implemented by a class tutor through an entire academic year. A qualitative case study research focused on the understanding of the relationship processes and of the solutions to the problems identified was adopted in order to grasp the meanings each actor (class tutor, parents, students and class teachers) ascribed to the events and processes related to school-family partnership, while connecting those meanings to the social context in which they lived. The analytical framework was mainly constituted a priori by categories derived from the ecological model of human development (Bronfenbrenner, 1979), the framework of six types of involvement (Epstein, 1997), and the theory of overlapping spheres of influence (Sanders and Epstein, 1998), complemented by data-driven categories and particular auxiliary theories.The findings of this study emphasized the importance of the frequency and diversity of school-family partnership activities in order to accommodate the specific needs of every family. The quality of communication and interpersonal relationships between the class tutor and parents plays a critical role in the development of trust and subsequently in partnership efficacy. Face-to-face contexts of communication are particularly effective.